Synergistic lignin construction of a long-chain branched polypropylene and its properties. Issue 62 (15th October 2020) - Tian, Bo; Li, Jinfeng; Li, Zhigang; Xu, Ningdi; Yao, Gang; Zhang, Nan; Dong, Wei; Liu, Yuguang; Di, Mingwei
Abstract : Polypropylene with long chain branching behavior was constructed by lignin, which foaming property and polarity were improved. Abstract : In light of current environmental pressures (referring to its destruction) and the consumption of petrochemical resources, the substitution of chemicals products with renewable natural substances has attracted extensive interest. In this paper, a synergistically constructed lignin polypropylene matrix composite with long-chain branched characteristics was prepared by a pre-irradiation and melt blending method. The effects of lignin on the crystallization, rheological behavior, foaming and aging properties of polypropylene were studied. Differential scanning calorimetry and polarized light microscopy results show that lignin undergoes heterophasic nucleation in a polypropylene matrix; rheological studies show that lignin promotes the formation of a heterogeneous polypropylene network, and thus polypropylene exhibits long-chain branching features; nucleation and a network structure endow the polypropylene-based composites with uniform cell size, thin cell walls, and a foaming ratio of 5–44 times; at the same time, a large number of hindered phenols in lignin can capture free radicals to improve the aging properties of the polypropylene. This research will help to convert industrial waste into functional composite materials.